A systematic review of the health, social and financial impacts of welfare rights advice delivered in healthcare settings - Howel Denise; Moffatt Suzanne; White Martin; Adams Jean; Mackintosh Joan (BMC, 2006)
Abstract Background Socio-economic variations in health, including variations in health according to wealth and income, have been widely reported. A potential method of improving the health of the most deprived groups is to increase their income. State funded welfare programmes of financial benefits and benefits in kind are common in developed countries. However, there is evidence of widespread under claiming of welfare benefits by those eligible for them. One method of exploring the health effects of income supplementation is, therefore, to measure the health effects of welfare benefit maximisation programmes. We conducted a systematic review of the health, social and financial impacts of welfare rights advice delivered in healthcare settings. Methods Published and unpublished literature was accessed through searches of electronic databases, websites and an internet search engine; hand searches of journals; suggestions from experts; and reference lists of relevant publications. Data on the intervention delivered, evaluation performed, and outcome data on health, social and economic measures were abstracted and assessed by pairs of independent reviewers. Results are reported in narrative form. Results 55 studies were included in the review. Only seven studies included a comparison or control group. There was evidence that welfare rights advice delivered in healthcare settings results in financial benefits. There was little evidence that the advice resulted in measurable health or social benefits. This is primarily due to lack of good quality evidence, rather than evidence of an absence of effect. Conclusion There are good theoretical reasons why income supplementation should improve health, but currently little evidence of adequate robustness and quality to indicate that the impact goes beyond increasing income.